Radiation exposure to the patient caused by single-photon transmission measurement for 3D whole-body PET - Schaefer, A.; Seifert, H.; Donsch, P.; Kirsch, C.-M. (Nuklearmedizin - NuclearMedicine, 2000)
Aim: The aim of the study was the determination of the radiation exposure to the patient caused by singlephoton transmission mesasurement for 3D whole-body PET. Material and Method: Single-photon-transmission measurement is performed using two Cs-137 pointsources (Eγ = 662 keV, A = 2*614 MBq) on a 3D PET scanner (ECAT ART). During a simulation of a whole body transmission scan (axial length: 75 cm, 6 contigous bed positions) dose measurements with thermoluminescent dosimeters were carried out using a thorax and an abdomen phantom. Following the guidelines of the ICRU report No. 60 an estimation of the effective dose caused by a single-photon transmission measurement was calculated. Results: For a total acquisition time of 360 min (6 beds with an acquisition time of 60 min per bed) the absorbed doses amounted to: surface (xyphoid) 189 μGy, heart 196 μGy, lungs 234 μGy, vertebra 240 μGy, liver 204 μGy, gonads 205 μGy, thyroid 249 μGy and bladder 185 μGy resulting in a conversion factor of 1.7*10–4 mSv/( h*MBq). The estimation of the effective dose for a patient’s transmission (acquisition time of 3.2 min per bed) yields a value of 11 μSv. An estimation of the ratio of the conversion factors for transmission measurements in single-photonand in coincidence mode (two Ge-68/Ga-68 rod sources of 40 MBq each), respectively, resulted in a value of 0.18. The comparison of the effective doses caused by single-photon transmission and by emission measurement (injection of 250 MBq of FDG) yields a ratio of 2.3*10–3. Conclusion: The radiation exposure of the patient caused by the transmission measurement for 3D whole-body-PET can be neglected. In comparison with the coincidence-transmission using uncollimated line sources of low activity the radiation exposure is still reduced using single photon transmission with collimated point sources of high activity.
Keywords: PET; transmission; single photon transmission; radiation exposure; thermoluminescence dosimetry